Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane